Arisaema longitubum (Araceae), a new species from northwestern Yunnan, China - Ma, Zheng-Xu (Phytotaxa, 2018)
Arisaema longitubum (Araceae), belonging to Arisaema sect. Odorata, is described and illustrated as a new species. The new species is closely related to Arisaema yunnanense, A. bathycoleum, and A. lidaense but differs in a suite of morphological characters useful in species distinction provided in this article.